Pengembangan Media Pembelajaran Matematika Tic Tac Toe Berbasis Etnomatematika Pada Materi Bangun Datar SMP Kelas VII - Mevianti, Amanda; Wiratomo, Yogi; Rasyid, H. Harun (Universitas Muhammadiyah Surabaya, 2024)
The purpose of this research is to develop mathematics learning media in the form of games to meet the needs of mathematics learning and can increase the interest and motivation of learning students. The subjects of this study were 33 grade VII students at SMP Negeri 1 Tajurhalang. This research uses a research and development approach by adapting the ADDIE model which includes 5 stages, namely, 1) Analyze, 2) Design, 3) Develop, 4) Implement, and 5) Evaluate. In this study, the product was validated to three material experts and three media experts and carried out individual trials for students. Based on the validation results from experts. The average assessment results from material experts received a score of 4.57 with the criteria of